GhTCP19 Transcription Factor Regulates Corm Dormancy Release by Repressing GhNCED Expression in Gladiolus. (6th September 2018) - Wu, Jian; Wu, Wenjing; Liang, Jiahui; Jin, Yujie; Gazzarrini, Sonia; He, Junna; Yi, Mingfang
Abstract: Dormancy is one of the least understood phenomena in plant biology; however, bud/corm dormancy is an important economic trait in agricultural/horticultural breeding. In this study, we isolated an ABA biosynthesis gene, GhNCED, from the transcriptome database of corm dormancy release (CDR), and characterized its negative role in regulating CDR. To understand transcriptional regulation of GhNCED, yeast one-hybrid screening was conducted and GhTCP19 was identified and shown to regulate GhNCED expression directly. An in planta assay showed that GhTCP19 negatively regulates GhNCED expression. GhTCP19 is dramatically induced by exogenous cytokinins (CKs) and is induced during CDR. Silencing of GhTCP19 in dormant cormels delayed CDR, resulting in higher expression of GhNCED and ABA levels. Meanwhile, endogenous CK biosynthesis and signaling were inhibited in GhTCP19 -silenced cormels. Taken together, our results reveal that GhTCP19 is a positive regulator of the CDR process by repressing expression of an ABA biosynthesis gene ( GhNCED ), promoting CK biosynthesis ( GhIPT ) and signal transduction ( GhARR ) as well as inducing cyclin genes. This study expands our knowledge on CDR which is mediated by TCP family members.